Epidemiological Indicators of SARS-CoV-2 (COVID-19) and Vaccination Effectiveness on the Report of Positive Cases in the Colombian Army - Duque, Maria Clara; Correa-Cárdenas, Camilo A.; Londoño-Méndez, Sebastián; Oliveros, Carolina; Pérez, Julie; Daza, Carlos D.; Albarracin, Lorena; Márquez, Elizabeth K.; Alvarado, Maria T.; Ortíz, Frank De Los Santos; Romero, Yanira; Gutierrez-Riveros, Sergio; et al. (Frontiers in Medicine, 2021)
The description of the epidemiological indicators of SARS-CoV-2 (COVID-19), such as the mortality rate (MR), the case fatality rate (CFR), and the attack rate (AR), as well as the geographical distribution and daily case reports, are used to evaluate the impact that this virus has had within the Colombian Army and its health system. As military forces around the world represent the force that defends sovereignty, independence, the integrity of the national territory, and the constitutional order, while maintaining migration controls in blocked border areas during this critical pandemic times, they must carry out strict epidemiological surveillance to control the situation among the servicemen. Up to date, the Colombian Army has faced a very high attack rate (AR = 8.55%) due, among others, to living conditions where active military personnel share bedrooms, bathrooms, and dining facilities, which facilitate the spread of the virus. However, being a mainly young and healthy population, the MR was 1.82 deaths/1,000 ha, while the CFR = 2.13% indexes consistently low if compared with those values reported for the national population. In addition, the effectiveness of vaccination is shown in daily cases of COVID-19, where, for the third peak, the active military population presented a decrease of positive patients compared to the dynamics of national transmission and the total population of the military forces (active, retired, and beneficiaries).